From Immigrants to University Students: Perceptions of Instructor Effectiveness Among Adult Emergent Bi/Multilingual Learners in the United States. Issue 2 (4th May 2021) - Housel, David A.
Abstract: With the changing demographics in postsecondary educational settings in the United States, including university students who do not speak English as their home language and must juggle multiple responsibilities along with their studies, are instructors adequately prepared to address the complex needs of their adult emergent bi/multilingual learners (EBLs)? This qualitative study explored the perceptions of four adult EBLs from different linguistic, cultural, and racial backgrounds from a large, urban area in the northeastern United States regarding their perceptions of the effectiveness of their instructors in addressing their diverse needs. Through semi-structured interviews and multiple rounds of coding, two broad themes emerged: qualities of "good" or "effective" instructors and the professionalism and overall preparedness of instructors. Preliminary suggestions advocate for providing more comprehensive preservice preparation and ongoing professional development for instructors of adult EBLs, especially university faculty, and fostering academic bi/multiliteracy among adult EBLs as areas worthy of future research.